Leadership commitment: a key factor in implementation of event-based cybersecurity risk assessment - Wan Mohamad, Wan Azlena; Abd Rahim, Noor Hayani; Abdul Molok, Nurul Nuha (Secholian Publication, 2025)
Implementing event-based cybersecurity risk assessment offers organisations a proactive approach to managing cyber threats in real-time. Unlike the asset-based approach, the event-based approach focuses on identifying and analysing potential cyber-attacks or events, rather than relying on static asset inventories. However, successful cybersecurity implementation relies not only on technical expertise but also on managerial expertise, such as strong leadership commitment. Leadership plays an important role in prioritising cybersecurity initiatives. It secures the necessary resources and ensures strategic integration into the organisation’s overall risk management framework. Despite its importance, limited research explores the impact of leadership commitment on implementing event-based cybersecurity risk assessment in organisations. This study uses a qualitative research approach to address this gap through semi-structured interviews with ten cybersecurity experts across multiple public sector organisations in Malaysia. Thematic analysis revealed three key leadership factors: (i) top management buy-in, which embeds cybersecurity into organisational priorities; (ii) resource allocation, which ensures adequate funding and support; and (iii) leadership advocacy, which maintains cybersecurity as a strategic agenda. These findings highlight that without strong leadership support, organisations may struggle to successfully implement event-based cybersecurity risk assessment. This study contributes to cybersecurity governance research by highlighting the critical role of leadership in adopting event-based cybersecurity risk assessment. It highlights the need for strategic leadership engagement in shaping cybersecurity policy, allocating resources and fostering a cyber risk-aware culture. The findings also provide practical insights for policymakers, cybersecurity professionals and organisational leaders in developing risk management frameworks to strengthen cybersecurity resilience